PERILAKU PEDAGANG KELILING DALAM MENGHADAPI PERSAINGAN (STUDI KASUS DI KABUPATEN BOJONEGORO) - Moch. Suberi (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2012)
Purpose of this study was to determine the behavior of itinerant traders in the market wares. and the face of increasingly fierce competition so as to maintain its business. based on research results of ten respondents inspiration mode is obtained from colleagues. 60% of respondents said the time to sell for about three to five years. Most 70% of the respondents informed that the merchandise or raw materials derived from the market town of Bojonegoro while 30% take raw materials from the distributor with a particular deal.